Thin film MOFs (SURMOFs) for application in gas separation - Valadez Sánchez, Elvia Patricia (KIT Scientific Publishing, 2019)
In this work, the deposition of ZIF-8 surface-anchored metal-organic framework (SURMOF) films was systematically studied. A proper characterization and optimization of the synthesized films was performed and their separation performance was determined. Furthermore, a general description of the system was achieved using the Maxwell-Stefan surface diffusion model.